Pengaruh Keputusan Pendanaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Kualitas Laba Sebagai Variabel Pemoderasi - Wardatul Jannah; Ahmad Juanda; Adi Prasetyo (Universitas Muhammadiyah Malang, 2019)
This research aims to know the influence of the dividend policy and funding decisions against the value of the company as well as an influence after the interaction of variable moderation that is the quality of the earnings. Types and sources of data obtained from the financial reports of the company property, real estate, and building construction 2016-2017 year published or to be published on the official website BEI ww.idx.co.id. Engineering data collection is done by the study of librarianship and documentation methods. Technique analysis on the research is conducting a classical assumption before multiple regression test was performed, and performed two model regression testing, i.e. the residual test and model test of interaction (MRA). Based on the results of the research, the author can provide a conclusion that funding decisions take effect against the value of the company, while the dividend policy has no effect against the value of the company. Results after the variable moderation that is giving interaction strengthen the relationship between the dependent variable independent variable.